Molecular Regulation of Endocytosis - Ceresa, Brian (IntechOpen, 2012)
Molecular Regulation of Endocytosis is a compilation of scientific "short stories" about the entry of external substances into cells. As one can see from the chapters, endocytosis regulates diverse processes such as homeostasis of the cell, signal transduction, entry of pathogens and viruses. In addition to the experimental techniques embedded in each chapter, entire chapters are dedicated to experimental approaches that will be useful to all scientists and their model systems. For those more clinically oriented, the final chapters look to the future and ways of utilizing endocytic pathways for therapeutic purposes.